Current state, comprehensive analysis and proposals on the practice of construction and demolition waste reuse and recycling in Portugal - Marinho, António Joaquim Coelho; Couto, João; Camões, Aires (Journal of Civil Engineering and Management, 2022)
The traditional method of construction and demolition waste (CDW) consumes a substantial amount of land resources causing severe environmental and social problems. In Portugal, the low recycling rate, combined with a high use of landfill as a way of managing CDW, has resulted in a negative index of 39% in the waste hierarchy, thus making it impossible for Portugal to be classified as a country that implements waste hierarchy in practice. The main goal of this study is to investigate the benefits of CDW reuse and recycling and the factors that promote or hinder this practice in Portugal. Therefore, a comprehensive approach has been adopted by combining the analysis of secondary data collected through extensive bibliography research with the results of a survey by questionnaire conducted on a group of experts in CDW management. It was concluded that the main method of CDW management consists of its disposal in licensed landfills (47%), and the rate of CDW reuse on site is still low (6%). The results show a high consistency between the respondents’ answers, as well as consistency between the opinions of these participants from different areas of professional activity. The respondents do recognize a concern regarding the reduction of carbon emissions, as well as a cultural resistance to materials or buildings that use CDW. These problems are further compounded by the difficulty in installing or supporting recycling equipment for CDW reuse on site. Respondents agree that there should be more investment and support from the government in this area, as well as in the training of construction companies.